SDN control solutions for an infrastructure supporting multimedia streaming flows - Tache, Maria-Daniela; Păscuțoiu, Ovidiu (Scientific Bulletin. Series C, Electrical Engineering and Computer Science, 2025)
The 5G technology offers today a powerful support for a large range of highlevel services, including media-oriented ones, for video, audio and voice flows. Within 5G management and control architecture, the Software-Defined Networking (SDN) technology has been proposed both in studies and standards, as a main component, while cooperating with Network Function Virtualization (NFV). For instance, in 5G slicing, an SDN-based control can play a major role, both at slice virtual tenant level and also at a lower infrastructure level, by dynamically managing network virtual or physical connectivity resources. Several types of SDN controllers are nowadays available. Which one to choose? This paper studies several solutions for SDN controllers, where they have the tasks to configure the SDN data plane transport media flows through SDN switches. The goal of this study is to prepare a SDN controlled infrastructure capable of supporting a study on Quality of Services (QoS) optimizations methods for multimedia streaming. Experiments have been defined and performed in this work, using some of the most common SDN controllers and an evaluation of their capabilities has been attempted. This study can provide real-life information to designers aiming to develop SDN controlled systems and particularly QoS optimized 5G slices for multimedia streaming.